TOXIC GAS SENSORS AND BIOSENSORS - INAMUDDIN (MATERIALS RESEARCH FORUM, 2021)
The book focuses on novel sensor materials and their environmental and healthcare applications, such as NO2 detection, toxic gas and biosensing, hydrazine determination, glucose sensing and the detection of toxins and pollutants on surfaces.